Bilateral cochlear implantation in a child with Waardenburg syndrome: A case report - Wang, Xiaohui; Xu, Lin; Zhang, Na; Zhao, Ying (Frontiers in Pediatrics, 2022)
Background: Waardenburg syndrome (WS) is a rare genetic disorder that presents with clinical characteristics such as white forelock, congenital deafness, dystopia canthorum, and heterochromia iridis. It is mostly transmitted through an autosomal dominant mode, with a few genetic mutations. Children with WS often require surgical intervention at an early age and may have a difficult airway, which can be challenging for anesthesiologists. Case presentation: We report the anesthetic management during cochlear implantation in a 14-month-old girl with WS who weighed 9 kg. In addition to hearing loss and delayed speech, she presented with motor developmental delay, chewing and swallowing impairments, and dietary bucking. Resistance was encountered during tracheal intubation after anesthesia induction, and the tracheal tube was successfully intubated after rotation. Conclusions: We report the anesthetic management during cochlear implantation in a child with WS, briefly describe the research advances related to WS, and discuss the optimization of the perioperative management of these children, including airway management, anesthesia-related complications, and the use of anesthetics.